PENGARUH MATERIAL RETURN TO WAREHOUSE, LEAD TIME, DAN FORECAST ACCURACY TERHADAP EFISIENSI PENGELOLAAN SPAREPARTS PADA PERUSAHAAN MANUFAKTUR - Muhammad Ludhiansyah Putra (CV. Lafadz Jaya, 2026)
Effective spare parts management plays an important role in supporting the operational activities of manufacturing companies. This study aims to analyze the effect of Material Return to Warehouse (MRW), Lead Time, and Forecast Accuracy on spare parts management efficiency. This research used a quantitative approach with multiple linear regression analysis. Data were collected through questionnaires distributed to respondents involved in spare parts management in manufacturing companies. The results show that Material Return to Warehouse, Lead Time, and Forecast Accuracy partially and simultaneously have a significant effect on spare parts management efficiency. Effective MRW management can improve inventory accuracy and optimize the utilization of available materials. In addition, proper lead time management and accurate forecasting systems also play an important role in improving spare parts inventory efficiency. The results of this study are expected to contribute to improving the effectiveness of inventory management systems and supporting the operational activities of manufacturing companies.